COMPARISON OF PAIN PERCEPTION IN CATARACT SURGERY WITH PHACO- HORIZONTAL-CHOP TECHNIQUE VERSUS VERTICAL-CHOP TECHNIQUE IN GRADE 3 CATARACT - Imam Masduki; Emelia, Dwi Ditha; Putri, Rachma Greta Perdana (Universitas Ahmad Dahlan, 2026)
Most cataract surgery is done by phacoemulsification method. Phacoemulsification cataract surgery with horizontal chop and vertical chop techniques is quite effective until now. In cataract surgery, generally used topical anesthetic pantocaine 0.5% (tetracaine 0.5%) to control pain in patients. This research aims to compare pain perception using a numeric rating scale in grade 3 cataracts operated by the phaco-horizontal-chop versus vertical-chop technique. This study is a comparative analytical study with a total of 87 subjects, consisting of 45 subjects undergoing surgery with the horizontal-chop technique, and 43 subjects with the vertical-chop technique. All patients were given the same topical anesthetic, pantocaine 0,5%. After the operation done, each subject will be asked about their pain perception using a numerical rating scale parameter. Then, the data were analyzed using univariate and bivariate analysis using chi-square. Among the 87 patients, mean pain scale in this study was 3.51, with a median value of 3.00. The minimum value of the pain scale was 1 while the maximum value was 6. The results showed that there was no significant relationship to pain experienced by patients undergoing phacoemulsification cataract surgery with the horizontal-chop technique compared with the vertical-chop (p = 1,000).